2015
DOI: 10.1016/j.antiviral.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine analogs and mycophenolic acid synergistically inhibit the papain-like protease of Middle East respiratory syndrome coronavirus

Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV) is a new highly pathogenic human coronaviruses that emerged in Jeddah and Saudi Arabia and has quickly spread to other countries in Middle East, Europe and North Africa since 2012. Up to 17 December 2014, it has infected at least 938 people with a fatality rate of about 36% globally. This has resulted in an urgent need to identify antiviral drugs that are active against MERS-CoV. The papain-like protease (PL(pro)) of MERS-CoV represents an important antiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
187
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(201 citation statements)
references
References 48 publications
(66 reference statements)
7
187
2
3
Order By: Relevance
“…[40][41][42][43][44][45] However,a few low-nm-range inhibitors have been identified that can be used in combination with other protease-inhibitor therapies to help combat the virus. Many of the inhibitors are in the micromolar range in terms of binding to and inhibiting the two proteases.…”
Section: Rna-dependent Rna Polymerasementioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42][43][44][45] However,a few low-nm-range inhibitors have been identified that can be used in combination with other protease-inhibitor therapies to help combat the virus. Many of the inhibitors are in the micromolar range in terms of binding to and inhibiting the two proteases.…”
Section: Rna-dependent Rna Polymerasementioning
confidence: 99%
“…In a FRET-baseda ctivity assay,t he IC 50 value of GC376a gainst recombinant SARS 3CLpro was found to be 4.9 times that against FIPV 3CLpro( 4.35 vs. 0.72 mm,r espectively). Arepresentation of the top CoV protease inhibitors providing ascaffold to perform SAR studies in termsofdesigning novel small-molecule protease inhibitors for 2019-nCoV [40][41][42][43][44][45]49] .3 CLpro-1, the most potent inhibitor,ish ighlighted. Figure 7.…”
Section: Rna-dependent Rna Polymerasementioning
confidence: 99%
“…Nonetheless, many antiviral agents have been identified, which have been summarized in several excellent reviews (Adedeji and Sarafianos, 2014;Keum and Jeong, 2012;Kumar et al, 2013;Liang, 2006;Ramajayam et al, 2011;Yang et al, 2006). Small molecules, such as 5chloropyridine ester, 6-mercaptopurine, and 6-thioguanine targeting MERS-CoV 3CL pro or PL pro have shown efficacy in inhibiting MERS-CoV replication in vitro (Chan et al, 2013;Cheng et al, 2015;Kilianski et al, 2013), though their activity and cytotoxicity needs to be further assessed in vivo. Small molecules, such as 5chloropyridine ester, 6-mercaptopurine, and 6-thioguanine targeting MERS-CoV 3CL pro or PL pro have shown efficacy in inhibiting MERS-CoV replication in vitro (Chan et al, 2013;Cheng et al, 2015;Kilianski et al, 2013), though their activity and cytotoxicity needs to be further assessed in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Although, MERS-CoV has been shown to antagonize endogenous interferon (IFN) production, treatment with exogenous types I and III IFN (IFN-α and IFN-λ, respectively) have effectively reduced viral replication in vitro.When rhesus macaques were given interferon-α2b and ribavirin and exposed to MERS, they developed less pneumonia than control animals (Falzarano et al, 2013). Researchers are investigating a number of ways to combat the outbreak of Middle East respiratory syndrome coronavirus, including using interferon, chloroquine, chlorpromazine, loperamide and lopinavir as well as other agents such as mycophenolic acid and camostat (Chan et al, 2015;Cheng et al, 2015).…”
Section: Treatmentmentioning
confidence: 99%